Development of a Local Potential-Based Problem-Based Learning E-Module for Ecology and Biodiversity: A Feasibility, Practicality, and Effectiveness Study - Syaukani, Muhammad Hafizh; Suyanta; Mahdian (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
The integration of contextualised digital learning resources with inquiry-oriented pedagogical frameworks represents a promising strategy for cultivating critical thinking skills and science literacy in secondary science education. This study reports the development and systematic evaluation of a Problem-Based Learning (PBL) e-module integrating the local ecological potential of North Hulu Sungai Regency — specifically the Swargaloka Amuntai nature reserve — for Grade VII ecology and biodiversity instruction under Indonesia's Merdeka Curriculum. Employing the ADDIE instructional design model, the study pursued three sequential objectives: (1) to assess expert-determined feasibility, (2) to evaluate teacher- and student-reported practicality, and (3) to examine classroom effectiveness via a quasi-experimental pre-test/post-test design involving 89 students across three instructional conditions (control, PBL e-module, PBL textbook). Expert validation yielded mean ratings of 3.3 (media) and 3.4 (subject matter), both within the 'very good' category, confirming instructional media quality. Practicality assessments by science teachers and students produced mean scores of 3.87–3.92 ('very good'), indicating strong contextual implementability. Quasi-experimental outcomes revealed medium-category normalised gain (N-gain) scores for critical thinking (0.52–0.61) and science literacy (0.56–0.64) across all groups; however, MANOVA analysis yielded non-significant between-group differences (p = 0.100; p = 0.190), indicating that the module did not produce statistically superior outcomes under the constrained conditions of a four-meeting implementation. These findings underscore the pivotal role of implementation duration, prior PBL exposure, and technology accessibility as moderating variables of e-module effectiveness, while affirming the module's validated quality and practical viability as a contextualised science learning resource.